Le uersus aureus comme structure annulaire - Antoine Foucher (Kentron)
In many aspects (verbal and syntactic construction, phonic organization), the golden line appears as a ring composition. It is probably even closer to the uersus teres that the grammarian Diomedes chose to illustrate with a golden line of Persius. In fact, the aesthetics of roundness or circularity are at the heart of the poetic project of certain poets of the Neronian period, Calpurnius Siculus in particular, and seem to correspond to certain dominant features of architecture of this time. However, the choice of a verse from Persius to illustrate this kind of verse perhaps also reveals the defects of too perfect roundness, as is also shown in a passage from the Satyricon.